Choosing an Exchange Rate Regime : The Challenge for Smaller Industrial Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This collection of papers, edited by Victor Argy and Paul De Grauwe, examines issues surrounding the choice of exchange rate regime in smaller industrial countries. It contains a comprehensive summary by Jacques J. Polak.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet